1999
DOI: 10.2307/2666998
|View full text |Cite
|
Sign up to set email alerts
|

Interorganizational Endorsements and the Performance of Entrepreneurial Ventures

Abstract: 1999 by Cornell University. 0001-8392/99/4402-031 5/$1 .00.We thank Ron Burt, Rob Gertner, Steve Kaplan, Jesper Sorensen, and Olav Sorensen for many helpful suggestions. We also thank Satomi Degami and Mark Edwards of Recombinant Capital for supplying us with information on private biotechnology firms, and Joshua Lerner for providing us with the equity index used in our analysis and for his extensive comments on this paper. Seminar participants at the Sloan School of Management, Harvard Business School, Haas S… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

50
1,932
8
26

Year Published

2000
2000
2008
2008

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 2,208 publications
(2,049 citation statements)
references
References 43 publications
50
1,932
8
26
Order By: Relevance
“…Past work has indicated that a scientist who is trained in the framework of drug discovery and development based on chemical synthesis loses on the average around 80-100 percent of his or her skills when attempting to transition to the emerging framework of drug discovery and development based on molecular biology (Rothaermel, 2001). The new biotechnology is thus considered to be competence destroying for pharmaceutical companies (Powell, Koput, and Smith-Doerr, 1996;Stuart, Hoang, and Hybels, 1999). Biotechnology firms possess R&D competences and capabilities that traditional pharmaceutical companies can profitably draw upon to maintain their innovative presence.…”
Section: Theory and Hypotheses Development Complementarities And Allimentioning
confidence: 99%
“…Past work has indicated that a scientist who is trained in the framework of drug discovery and development based on chemical synthesis loses on the average around 80-100 percent of his or her skills when attempting to transition to the emerging framework of drug discovery and development based on molecular biology (Rothaermel, 2001). The new biotechnology is thus considered to be competence destroying for pharmaceutical companies (Powell, Koput, and Smith-Doerr, 1996;Stuart, Hoang, and Hybels, 1999). Biotechnology firms possess R&D competences and capabilities that traditional pharmaceutical companies can profitably draw upon to maintain their innovative presence.…”
Section: Theory and Hypotheses Development Complementarities And Allimentioning
confidence: 99%
“…Second, researchers have explored the deal-specific and competitive conditions that engender governance choices in alliance agreements, such as the decision to take a partial ownership stake in a partner (e.g., Pisano, 1989Pisano, , 1991Robinson and Stuart, 2007). Third, a number of studies have gauged the consequences of collaborative activity for firm-level performance outcomes, including the rate of innovation (Shan et al, 1994), growth (Powell et al, 1996), valuations of early stage companies (Stuart et al, 1999), and the adaptability of established organizations (Rothaermel, 2002).…”
Section: Introductionmentioning
confidence: 99%
“…5 The F-statistic reported is from a test of the hypothesis that of the slope coefficients (excluding the constant) in the regression are zero. 6 Critical value at 5 per cent of significance level from F-distribution.…”
Section: Regression Resultsmentioning
confidence: 99%
“…First of all, access is gained to complementary assets 4,5 and, second, clear signals about a company's status are sent by aligning with 'renowned actors'. 6 Incumbents (TPCs) with complementary assets, in particular when they specialise in the commercialisation of innovations, with competencies in manufacturing or marketing, are well positioned to benefit from radical technological changes in biotechnology. From a financial perspective, NBFs often fall between the cracks of traditional funding sources and from a management perspective they often lack managerial expertise.…”
Section: Fundamental Benefitsmentioning
confidence: 99%